Analisis Multidimensional Scaling pada Pemetaan Kabupaten/Kota di Provinsi Sumatera Barat Berdasarkan Fasilitas Kesehatan - Marwiyah, Leli; Murni, Dewi (UNIVERSITAS NEGERI PADANG, 2024)
Health facilities are places used for organize health efforts carried out by the government, local government and the community. The existence of health facilities illustrates how the process of fulfilling health needs in an area. According to the West Sumatra provincial health office, access to health services is hampered due to the limited number of health care facilities. This research was conducted using the multidimensional scaling method. This type of research is applied research. Based on the map generated by the MDS analysis, it was found that districts/cities that have similar characteristics of health facilities are Bukittinggi City, Sawahlunto City, Pariaman City, Solok City, Payakumbuh City, Padang Panjang City, Mentawai Islands Regency, Dharmasraya Regency and Sijunjung City: Pasaman Regency, Regency of South Solok and Tanah Datar Regencies. City Districts that need to be considered for the characteristics of health facilities are Agam District and Maternity Homes. District of Fifty Cities to Hospitals, Maternity Hospitals, Special Hospitals. Tanah Datar Regency to the Clinic.